Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12886-021-01909-3
|View full text |Cite
|
Sign up to set email alerts
|

Visual assessment of commercial drivers in the South West Region of Cameroon

Abstract: Background Driving is a visually intensive task. In Cameroon, where the burden of road traffic deaths is high, visual assessment is not universally performed before the issuance of driver licenses. This study aims to assess the visual status of commercial drivers (CDs) in the southwestern region of Cameroon, and to find its relation to road traffic crashes (RTCs). Methods This work was a cross-sectional community-based study on CDs in Limbe and Bue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…[ 25 26 27 28 29 ] Two recent studies from Africa have reported a strong association between poor vision among drivers and RTA. [ 22 28 ] Findings from our study highlight a clear and significant association between RE and RTA. CTDs with any type of RE in at least one eye had the highest odds of experiencing RTAs.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[ 25 26 27 28 29 ] Two recent studies from Africa have reported a strong association between poor vision among drivers and RTA. [ 22 28 ] Findings from our study highlight a clear and significant association between RE and RTA. CTDs with any type of RE in at least one eye had the highest odds of experiencing RTAs.…”
Section: Discussionmentioning
confidence: 55%
“…[ 11 ] Most of the scientific evidence on the ocular morbidities including RE among commercial drivers emanate from African countries which report a RE prevalence ranging from 30% to 60%. [ 4 20 21 22 23 24 ] Higher rates of RE reported in all of these various studies, including ours, make CTDs a priority group for targeted eye-care interventions. Owing to their constant mobile and busy lifestyles, CTDs are quite often unable to utilize the existing health care systems.…”
Section: Discussionmentioning
confidence: 75%
“…VA (28 studies, n=39 129) was not found to be associated with crash involvement by 19 studies,17 20 22 24 27–29 31 33–36 38 40 41 45 50–54 57 63 68 69 73 75 77 80 irrespective of crash scenario (at fault or not at fault) and severity (injurious or non-injurious). Bilateral VA 20/40 or worse may impact risk of MVCs (meta-analysis five studies; RR 1.21 (95% CI 1.02 to 1.43); p=0.03) 27 31 40 73 77.…”
Section: Resultsmentioning
confidence: 97%
“…Raw data on studies reporting on MVCs15–81 and driving cessation70–73 82–115 can be found in online supplemental appendix 4A,B, respectively, with additional narrative summaries. Meta-analyses on associations are presented in online supplemental appendix 5A,B; only 25 studies could be meta-analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation